Статистична теорія фазових переходів у двокомпонентних плинах: метод колективних змінних - Пацаган, О. (Праці наукового товариства ім. Шевченка, 2011)
We give an overview of a number of works devoted to the development of the microscopic theory of phase transitions in two-component fluids. The theory is based on the method of collective variables (CVs) developed by academician I.R. Yukhnovskii. The main emphasis is made on the problems in whose solution the CV method appears to be more effective than other theoretical approaches.